Comparing the Effectiveness of Guttman Model and Emotion-Focused Therapy on Couples’ Loneliness and Resilience - Daryaye Lal, Azita; Akbari, Bahman; Sadeghi, Abbas (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to compare the effectiveness of Guttman model and emotion-focused therapy on loneliness and resilience of couples. Methods: The research method was semi-experimental with pre-test, post-test and follow-up with the control group. The statistical population of this study included all couples referred to clinics west of Tehran in 2020 who were selected by convenience sampling method, 24 couples (48 persons) and randomly divided into two groups of intervention by Guttman couple therapy, emotion-focused therapy and a control group (8 couples in each group). The experimental group underwent 10 sessions of 90 minutes of couple therapy and Guttman’s (2017) emotion-focused therapy Greenberg (2017), and the control group remained on the waiting list. Data were collected based on loneliness questionnaire DiTommaso, Brannen, & Best (2004) and resilience questionnaire Conner & Davidson (2003) and SPSS software and variance analysis method with repeated measurements were used. Results: The results showed that Guttman’s model method and emotion-focused therapy had an effect on loneliness (F=28.05, P=0.001) and resilience (F=11.85, P=0.001) of couples, and this effect was found in the follow-up phase (P<0.05). However, there was no significant difference between the two treatments in terms of effectiveness. Conclusion: Based on the findings of this study, it can be said that Guttman’s model method and emotion-focused therapy based on loneliness and resilience of couples is an effective model for increasing couples’ marital satisfaction and it can be used as one of the therapeutic or educational methods in couple therapy programs.